2011
DOI: 10.3382/ps.2010-01098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein level and digestibility on the growth and carcass characteristics of broiler chickens1

Abstract: A study was conducted to evaluate the effects of dietary protein level and protein digestibility on the growth performance and carcass characteristics of broilers from 1 to 35 d of age. Broiler chickens (n = 320) were fed 4 different ideal protein-balanced, isocaloric diets in a 2 × 2 factorial design with 2 levels of protein [high protein (HiPro; 20 and 18% or 200 and 180 g/kg) and low protein (LoPro; 18 and 16% or 180 and 160 g/kg) on d 1 to 14 and d 15 to 35, respectively] and 2 levels of protein digestibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 37 publications
8
25
0
1
Order By: Relevance
“…In our trial, in general, there are few differences among groups in terms of fat deposition and percentage of liver. The results on abdominal fat deposition are in line with the findings of Widyaratne & Drew (2011). Also the effect of liver fat percentage is not linear but the groups supplemented with 4% CLA had a higher liver fat percentage than the correspondent low-CP groups no supplemented with CLA, and, for the 5EAAs group, also higher than the control.…”
Section: Discussionsupporting
confidence: 79%
“…In our trial, in general, there are few differences among groups in terms of fat deposition and percentage of liver. The results on abdominal fat deposition are in line with the findings of Widyaratne & Drew (2011). Also the effect of liver fat percentage is not linear but the groups supplemented with 4% CLA had a higher liver fat percentage than the correspondent low-CP groups no supplemented with CLA, and, for the 5EAAs group, also higher than the control.…”
Section: Discussionsupporting
confidence: 79%
“…According to Laudadio et al (2012) feeding dietary protein levels (20.5%) under thermoneutral conditions significantly improved the growth of broilers compared to levels of 22.5 and 18.5%, whereas BWG and feed intake and FCR remained unaffected by dietary treatment during 14-49 d of age. On the other hand, low-protein diets can sustain productive performance similar to highprotein diets (Widyaratne and Drew 2011). In this regard, ileum villi did not alter by feeding with the low-CP diet.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, the effect of the dietary CP of broilers was found to be inconsistent and differed from one study to another; for example, utilisation of low-CP diets for broiler chickens caused low performance compared to standard protein with sufficient amino acids (Berres et al 2010). On the other hand, Laudadio et al (2012) and Widyaratne and Drew (2011) found that low-protein diets under thermoneutral conditions did not influence the performance of broilers. Alternatively, in hot climates, low dietary protein increased growth performance (Thim et al 1997).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the increase FI with diets T2 and T3 can be an attempt by the birds to meet their nutrient requirements (Hill and Dansky, 1954). According to Widyaratne and Drew (2011) FI is influenced by the availability and quality of dietary protein particularly lysine in the amino acid concentration, however, due to the high tannin content from the increase levels of S.molesta as well as crude fiber contents of diets T2 and T3 this could have reduced the amount of dietary lysine hence the birds increased their FI but still their nutrient requirements were not met as evident with the suppressed growth rate with treatments T2 and T3. This is in line with Uwalaka et al (2013) who observed that increased level of tannin content in unripe plantain peel meal (UPPM) caused the birds to increase their FI but still resulted in depressed weight gain of broilers.…”
Section: Performancementioning
confidence: 99%